PERKEMBANGAN PEMIKIRAN MANAJEMEN STRATEGI ( Dari Fragmentasi Menuju Integrasi ) - Wahyudi, Amin (Joglo, 2010)
ABSTRACT The study about strategic management theory  growth continually. Many expert have told various strategy management,  growth model and approach. Growth thinking of dynamic Management Strategy that way and very influenced by environmental growth of company which also growth dynamicly and continually. The Growth show the existence of change from pragmentasi  to toward integration thereby, can be created by a strategic management which have sturdy conceptual framework and accurate methodologies. Strategic management relate to strategy implementation and development in excellence development framework compete. More than that, strategy management  have importance  with clarification to the excellence development compete to have continuation (sustainable competitive advantage ) Keyword : Strategic Management, sustainable competitive advantage